2013
DOI: 10.1037/a0033004
|View full text |Cite
|
Sign up to set email alerts
|

Are the parts as good as the whole? A meta-analysis of component treatment studies.

Abstract: These findings suggest that added specific ingredients may contribute modestly to treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
162
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 96 publications
8
162
1
6
Order By: Relevance
“…Given the level of standardization found in the IC arm of this study and in similarly constructed guided IBI, the guidance itself oftentimes consists of individualizing only a minor amount of text and might thus be considered a small “add-on” to already effective treatments. Consequently, our results are in line with meta-analytic comparisons of component treatment studies suggesting that added components yield very small effects [70] or no effects at all [71]. …”
Section: Discussionsupporting
confidence: 78%
“…Given the level of standardization found in the IC arm of this study and in similarly constructed guided IBI, the guidance itself oftentimes consists of individualizing only a minor amount of text and might thus be considered a small “add-on” to already effective treatments. Consequently, our results are in line with meta-analytic comparisons of component treatment studies suggesting that added components yield very small effects [70] or no effects at all [71]. …”
Section: Discussionsupporting
confidence: 78%
“…This result points to the added value of MOTR when integrated or combined with an established treatment form. The effect sizes of the present add-on study are slightly larger than reported in a recent meta-analysis on all additive studies in psychotherapy (d = 0.14 and d = 0.28), which are interpreted as small but significant additive improvements [50]. Larger effect sizes in our study might be due to the specific nature of MOTR, a relationship technique much closer to what Ahn and Wampold [51] called the common factors in psychotherapy.…”
Section: Discussioncontrasting
confidence: 41%
“…A next step is to determine the mechanisms of change in multicomponent PPIs. Therefore, it is necessary that future studies use a more complex design, for example by using at least a 6-armed trial wherein one component is added to each intervention arm (from one component to all six components; additive design) or wherein each component is examined in isolation and compared to the comprehensive intervention (dismantling design) (Bell, Marcus, & Goodlad, 2013).…”
Section: Disclosure Statementmentioning
confidence: 99%